Relationship between Income inequality and health in Iran during 1976-2006 - M Babakhani (مدیریت سلامت, 2009)
Introduction: With changing pattern of diseases from infectious to chronic, the role of psychological and social determinants of health (SDH including distribution of income (income inequality) have found importance. Severe income inequality indicates the decrease in income available to the majority of people in society with its negative effects on health. Income inequality in society, increases the feeling of deprivation, and influences mental health in the society. This study was aimed to find relation between incomes inequality and health in Iran during 1976-2006. Methods: This is an analytical - ecological correlation study. Unit of analysis are the Iran the population , and data are obtained the SCI and the Central Bank of Iran. For data analysis Pearson regression by SPSS software was used. Results: Gini coefficient relationship with life expectancy is found significant(p=0.0001, r=-0.83). Relation between Gini coefficient and under 5 years mortality rate is also significant (p=0.0001, r=0.87). Conclusion: In the studied time period, with increasing income inequality, life expectancy has decreased and under 5 years mortality rate has increased. In order to improving and enhancing community health people and reducing income inequality it appears that to adopt appropriate redistributive incomes policies is required.